2016
DOI: 10.1136/vetreccr-2016-000317
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset wedge‐shaped thoracic vertebrae in a six‐month‐old pug

Abstract: A six-month-old pug was presented with kyphosis and pelvic limb lameness. During a routine neurological and radiographic screening of the vertebral column at two months of age, no congenital abnormalities were noted. Four months later, radiography showed marked kyphosis of the thoracic vertebral column with wedge-shaped T8 and T9. After euthanasia, gross examination and CT revealed the same findings as on radiology. Histopathology of the wedge-shaped vertebrae T8 and T9 showed abnormal caudal growth plates pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Binary logistic regression however indicated that higher age and occurrence of spinal kyphosis should both be considered independent and non-related risk factors for occurrence of IVDE in FBs. It can also not be excluded that some dogs would have developed more severe degrees of kyphosis later in life [ 29 , 30 ]. Control dogs underwent CT, while dogs with IVDE underwent MRI as the most appropriate diagnostic technique for their respective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Binary logistic regression however indicated that higher age and occurrence of spinal kyphosis should both be considered independent and non-related risk factors for occurrence of IVDE in FBs. It can also not be excluded that some dogs would have developed more severe degrees of kyphosis later in life [ 29 , 30 ]. Control dogs underwent CT, while dogs with IVDE underwent MRI as the most appropriate diagnostic technique for their respective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Kyphosis and scoliosis can change as an animal matures, which can alter spinal biomechanics, as shown in a case report of a 6-month-old pug with kyphosis that was not present on radiographs at 2 months of age. 22 Almost three quarters (8 of 11, 72%) of the dorsal wedge vertebrae were found within 1-2 vertebral bodies from a ventral wedge malformation and it is theorised that they might have developed secondarily as a result of abnormal biomechanical pressures created from the kyphosis caused by an adjacent ventral wedge or other malformations (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] In process dysplasias, are difficult to document without CT. 3 Although a previous study, including pugs of similar age as in the present study, could not confirm an association between CVMs and neurological signs, it has been suggested that some CVMs in pugs are indeed clinically significant. 10,11,18 Vertebral malformations, congenital or potentially acquired, 53 may inflict direct spinal cord trauma by chronic micromotion as a consequence of vertebral canal stenosis or instability, or indirect trauma by negatively interfering with its vascular supply and thereby limiting its resistance to injury. 4,7,11,14,[54][55][56] Spinal cord dynamic compression occurs in pugs with SAD and repetitive spinal cord injury could be a potential cause of thoracolumbar SADs.…”
Section: Macroscopic Findingsmentioning
confidence: 99%